Profil Proses Berpikir Kreatif Dalam Pemecahan Masalah Matematika Berdasarkan Teori Wallas Pada Siswa Kelas VIII SNP Negeri 24 Makassar - Muhammad Rispandi; Muhammad Rizal Usman (JURNAL MathEdu (Mathematic Education Journal), 2020)
This study attempts to knowledge and the capacity to think creative described students in solving mathematical problems based on theories wallas students VIII class SMPN Makassar 24 high representatives, medium and low. The research is the qualitative study designed to have a creative thinking a subject in solving a problem based on a theory Wallas mathematics.The data processed creative thinking in the solution is a process based on a theory Wallas mathematical problems.Technique used is the data collection test, and interview. About used the measures the solving a problem in an essay were about 3 number of matter relation and functions. Interview aims to have a creative thinking a subject in solving a problem based on a theory Wallas mathematics. Based on the data, processed obtained that subject representatives high at subject understand the problems and information That was given at about and also able to wrote indicated and asked in about (preparation) , the subject did not takes a long time to get the idea to address the issues (incubation) period is complete , the subject of able to get an idea to solve problems (of illumination) , the subject test ideas and check return for an answer obtained to obtain conclusion .The subject who performed well being the subject of trying to understand the problem but the subject are in doubt as to what made known ( preparation ) , the subject of trying to remember what has been taught before , but it also costs a long time even subject is leaving for a moment about other things to do (incubation) period is complete , the subject came up with this idea from the results of the incubation period is complete to solve the problems that given (of illumination) . The subject tends to result in check return for an answer because the subject already convinced whose answer already written (verification) .The subject who performed well low , the subject did not ready to answer about given because the subject have repeatedly read that situation but not understand a problem well (preparation) the subject needs a long time to think of solutions provided, from trouble even a subject see a printed book to resolve that situation (incubation) subject to produce an idea he found a printed book without bias explained how to get the value of the (illumination) the subject is not check returning the answer he wrote for sure answers that he had written because it comes from a printed book mathematics (verification).